THE IMPACT OF SOCIAL MEDIA NEWS COVID-19 ON THE DECREASE OF TOURISM ACTIVITIES IN MEDAN CITY IN THE SOCIAL ECONOMIC ASPECTS OF THE COMMUNITY - H Silaban, Pantas; Fila Sari Saragih, Agitha; Peranginangin, Chandra; Manalu, Palti; F.D. Silalahi, Chandra (RADJA PUBLIKA, 2022)
This study aims to get an overview of the initial impact of the COVID-19 pandemic on North Sumatra tourismby using research methods is the whole way of thinking used by researchers to find answers to research questions, including the approach used, scientific procedures (methods taken) including in collecting data, analyzing data and drawing conclusions. This type of research is descriptive. The purpose of descriptive research is to make descriptions, pictures, or paintings in a systematic, factual and accurate manner regarding the facts, characteristics and relationships between the phenomena being investigated.The primary data source in this research is data obtained from informants. Primary data collection using interviews with research informants. The collection method is structured and open, meaning that respondents are informed about the research objectives so that they can provide answers in accordance with the research objectives and do not deviate which can result in biased research results. The results and discussion can be concluded that the impact of covid-19 on West Sumatra tourism has caused a decrease in foreign tourists and foreign tourists visiting, a decline in the transportation sector and the provision of accommodation and food and drink. This in turn also has an impact on the poor condition of employment in the tourism sector in West Sumatra. Entrepreneurs generally find it difficult to finance operationsbusiness, experienced a decrease in income and losses due to no business income. The impact caused by the COVID-19 pandemic shows that tourism, which has links with many supporting sectors, is a sector that is very vulnerable to disasters such as disease outbreaks or pandemics.